2013
DOI: 10.1128/aem.01937-13
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of the Alga-Associated Marine Flavobacterium Formosa agariphila KMM 3901 T Reveals a Broad Potential for Degradation of Algal Polysaccharides

Abstract: In recent years, representatives of the Bacteroidetes have been increasingly recognized as specialists for the degradation of macromolecules. Formosa constitutes a Bacteroidetes genus within the class Flavobacteria, and the members of this genus have been found in marine habitats with high levels of organic matter, such as in association with algae, invertebrates, and fecal pellets. Here we report on the generation and analysis of the genome of the type strain of Formosa agariphila (KMM 3901 T ), an isolate fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
156
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(167 citation statements)
references
References 81 publications
6
156
0
1
Order By: Relevance
“…Studies have shown that Bacteroidetes bacteria are common in marine environments (791), abundant in organic particle-rich coastal waters (108,113,130,611,791), responsive to algal and jellyfish blooms (272,537,756,(791)(792)(793), copiotrophic (252), and prone to leading a surface-associated life (12,17,246,272,574,607) supported by the extracellular degradation of complex biopolymers such as polysaccharides and proteins (194,791,(794)(795)(796)(797). These bacteria harbor a large number of genes for adhesive exopolysaccharides, adhesion proteins, proteases, peptidases, glycoside hydrolases, and lipases, and several genes for biopolymer degradation are coregulated with the genes for TonBdependent transport systems (794,795,(798)(799)(800)(801)(802). These properties indicate that the marine Bacteroidetes are specialists in surface colonization and play a key role in the degradation and utilization of HMW DOM and POM (272,791).…”
Section: Marine Bacteroidetesmentioning
confidence: 99%
“…Studies have shown that Bacteroidetes bacteria are common in marine environments (791), abundant in organic particle-rich coastal waters (108,113,130,611,791), responsive to algal and jellyfish blooms (272,537,756,(791)(792)(793), copiotrophic (252), and prone to leading a surface-associated life (12,17,246,272,574,607) supported by the extracellular degradation of complex biopolymers such as polysaccharides and proteins (194,791,(794)(795)(796)(797). These bacteria harbor a large number of genes for adhesive exopolysaccharides, adhesion proteins, proteases, peptidases, glycoside hydrolases, and lipases, and several genes for biopolymer degradation are coregulated with the genes for TonBdependent transport systems (794,795,(798)(799)(800)(801)(802). These properties indicate that the marine Bacteroidetes are specialists in surface colonization and play a key role in the degradation and utilization of HMW DOM and POM (272,791).…”
Section: Marine Bacteroidetesmentioning
confidence: 99%
“…In support of this, the proteomics approach did not show any carbohydrate uptake systems or carbohydrate-utilizing proteins being upregulated in M. adhaerens HP15 in the presence of the diatom. The findings were further substantiated by the remarkably low number of carbohydrate utilization-associated proteins encoded by the genome of M. adhaerens HP15, as compared to those of classical degraders of algae exudates, such as Flavobacterium johnsoniae UW101 (McBride et al 2009) or other members of the Flavobacteria (Mann et al 2013).…”
Section: Adhaerens Hp15 Is Not a Carbohydrate Degradermentioning
confidence: 90%
“…Consequently, the majority of these carbohydrates were considered experimentally in the present study. Certain bacterial groups, such as members of the Bacteroidetes, are known for their ability to degrade carbohydrate compounds resulting from algae exudates (Teeling et al 2012, Mann et al 2013). According to our proteomics and carbon utilization results, none of the tested carbohydrates was used as a carbon source by M. adhaerens HP15 except for fructose.…”
Section: Adhaerens Hp15 Is Not a Carbohydrate Degradermentioning
confidence: 99%
“…Bacteroidetes are particularly rich in carbohydrate-assimilation TBDT (Blanvillain et al, 2007;González et al, 2008;Hehemann et al, 2010;Tang et al, 2012) and biopolymer degradation enzymes (McBride et al, 2009;Hehemann et al, 2010;Qin et al, 2010;Thomas et al, 2012;Mann et al, 2013). Many Bacteroidetes glycoside hydrolase genes are organized in polysaccharide utilization loci, usually clustered with genes for TonB-dependent receptors, SusD-like proteins, sensors/transcription factors, transporters and frequently with genes for sulfatases (McBride et al, 2009;Hehemann et al, 2010;Qin et al, 2010;Thomas et al, 2012;Fernández-Gómez et al, 2013;Mann et al, 2013).…”
Section: Tonb-dependent Transportersmentioning
confidence: 99%
“…Environmental sequences of Bacteroidetes TBDT-related proteins, genes and their transcripts have been frequently found in abundance in metaproteomic, metagenomic and metatranscriptomic sequences from various ocean habitats, especially in coastal waters (Morris et al, 2010;Ottesen et al, 2011;Tang et al, 2012). Bacteroidetes also harbor diverse genes for the degradation of proteins, chitin and bacterial cell wall peptidoglycans (Cottrell and Kirchman, 2000;McBride et al, 2009;Qin et al, 2010;Gómez-Pereira et al, 2012;Mann et al, 2013). Thus, Bacteroidetes have been regarded as specialists for degradation of HMW biomacromolecules in both the particulate and dissolved fraction of the marine OM pool (Bauer et al, 2006).…”
Section: Tonb-dependent Transportersmentioning
confidence: 99%